A novel bowel rehabilitation programme after total mesorectal excision for rectal cancer: the BOREAL pilot study. (2nd August 2021) - Harji, Deena; Fernandez, Benjamin; Boissieras, Lara; Berger, Arthur; Capdepont, Maylis; Zerbib, Frank; Rullier, Eric; Denost, Quentin
Abstract: Aim: Low anterior resection syndrome (LARS) following sphincter‐preserving surgery for rectal cancer has a high prevalence, with an impact on long‐term bowel dysfunction and quality of life. We designed the bowel rehabilitation programme (BOREAL) as a proactive strategy to assess and treat patients with LARS. The BOREAL programme consists of a stepwise approach of escalating treatments: medical management (steps 0–1), pelvic floor physiotherapy, biofeedback and transanal irrigation (step 2), sacral nerve neuromodulation (step 3), percutaneous endoscopic caecostomy and anterograde enema (step 4) and definitive colostomy (step 5). Methods: A pilot study was undertaken to assess the feasibility of collecting LARS data routinely with the parallel implementation of the BOREAL programme. All patients who underwent total mesorectal excision for rectal cancer between February 2017 and March 2019 were included. LARS was assessed using the LARS score and the Wexner Faecal Incontinence score at 30 days and 3, 6, 9 and 12 months postoperatively. A good functional result was considered to be a combined LARS score <20 and/or a Wexner score <4. Results: In all, 137 patients were included. Overall compliance with the BOREAL programme was 72.9%. Major LARS decreased from 48% at 30 days postoperatively to 12% at 12 months, with a concomitant improvement in overall good function from 33% to 77%, P < 0.001. The majority of patients ( n = 106, 77%) required medical management of their LARS. Conclusion: The BOREAL programme demonstrates the acceptability, feasibility and effectiveness of implementing a responsive, stepwise programme for detecting and treating LARS.